1964
DOI: 10.1128/jb.88.4.877-884.1964
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Leptospiral Lipase

Abstract: A technique for leptospiral lipase extraction which yielded a highly active, stable, and concentrated lipase preparation was developed. The chief characteristics of leptospiral lipase were determined and are summarized below. Leptospiral lipase was soluble in water and stable in both the dry state

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

1969
1969
1986
1986

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Serotype L. pomona LC-12 was the source of the leptospiral lipase. The growth medium and conditions of culture and methods of isolation were as previously described (14). Lipase activity.…”
Section: Materils and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotype L. pomona LC-12 was the source of the leptospiral lipase. The growth medium and conditions of culture and methods of isolation were as previously described (14). Lipase activity.…”
Section: Materils and Methodsmentioning
confidence: 99%
“…The first detailed attempt at characterization of the leptospiral lipase was carried out in this laboratory (14). Ethyl alcohol and acetone extraction and freeze-drying produced a brown powder, stable in dry and liquid states, which had maximal activity at pH 8 and 30 C; it was not inhibited by metals, proteolytic enzymes, or -SH blocking agents, and possessed a Michaelis constant of 4.76 X 102.…”
mentioning
confidence: 99%
“…It has been observed that precipitation of the proteins from leptospiral culture fluids by large excesses of ethanol does not increase lipase specific activity (2,3,12). However, the precipitate resulting at 10% (v/v) ethanol concentrations was 14-fold higher in specific activity ( Table 1).…”
mentioning
confidence: 97%
“…Leptospirae occur in the mammalian circulation where free fatty acid concentration is relatively low. The lipases (EC 3.1.1.3) secreted by leptospirae convert triglycerides to fatty acids (2,3,5,9,12). Concentrates of the enzyme have been prepared from culture media by repeated ethanol precipitation, dialysis, and lyophilization (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation